Bioresorbable Scaffold: The Emerging Reality and Future Directions. Issue 8 (14th April 2017) - Sotomi, Yohei; Onuma, Yoshinobu; Collet, Carlos; Tenekecioglu, Erhan; Virmani, Renu; Kleiman, Neal S.; Serruys, Patrick W.
Abstract : In the era of drug-eluting stents, large-scale randomized trials and all-comer registries have shown excellent clinical results. However, even the latest-generation drug-eluting stent has not managed to address all the limitations of permanent metallic coronary stents, such as the risks of target lesion revascularization, neoatherosclerosis, preclusion of late lumen enlargement, and the lack of reactive vasomotion. Furthermore, the risk of very late stent, although substantially reduced with newer-generation drug-eluting stent, still remains. These problems were anticipated to be solved with the advent of fully biodegradable devices. Fully bioresorbable coronary scaffolds have been designed to function transiently to prevent acute recoil, but have retained the capability to inhibit neointimal proliferation by eluting immunosuppressive drugs. Nevertheless, long-term follow-up data of the leading bioresorbable scaffold (Absorb) are becoming available and have raised a concern about the relatively higher incidence of scaffold thrombosis. To reduce the rate of clinical events, improvements in the device, as well as implantation procedure, are being evaluated. This review will focus on the current CE-mark approved bioresorbable scaffolds, their basic characteristics, and clinical results. In addition, we summarize the current limitations of bioresorbable scaffold and their possible solutions. Abstract : Supplemental Digital Content is available in the text.